A NEW CONCEPTUAL FRAMEWORK FOR ENHANCING EMPLOYABILITY SKILLS AMONG HIGHER VOCATIONAL STUDENTS BASE ON GROUP WORK INTERVENTIONS - Hua, Jin; Hussin, Hanipah; Yueying, Yang; Lusi, Zhang (Journal of Human Capital Development (JHCD), 2023)
This paper aims to describe a new conceptual framework for enhancing employability skills based on group work interventions. The research design used is an experiential learning design and was conducted through explanatory research, which combines both qualitative and quantitative research methods. Higher vocational students were used as research subjects, and group dynamics theory was used as the theoretical basis. Data were collected using questionnaire surveys, interviews, group work methods, and experimental research. A new conceptual framework for enhancing employability skills was developed by selecting 40 fresh graduates from Jiangmen Polytechnic to participate in a 2-month employability skills promotion group work activity. The new conceptual framework clarifies the variables and characteristics that affect the improvement of employment skills and reveals the relationships between the variables. The findings present a new conceptual framework for improving the employability skills of higher vocational students based on group work interventions and describe the variables and characteristics within this framework. This research significantly contributes to the field, equipping educators and organizers with the knowledge to create tailored programs for enhancing employability skills among higher vocational students.Ultimately, these efforts aim to empower students with the necessary competencies to thrive in the dynamic job market and embark on successful career paths. Keywords: conceptual framework; employability skills; group work intervention